2012
DOI: 10.1371/journal.pone.0040631
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Thermal and Spectral Properties of Er3+-Doped and Er3+/Yb3+-Codoped Li3Ba2La3(WO4)8 Crystals

Abstract: This paper reports the growth and spectral properties of Er3+-doped and Er3+/Yb3+-codoped Li3Ba2La3(WO4)8 crystals. The Er3+: Li3Ba2La3(WO4)8 crystal with dimensions of 56 mm×28 mm×9 mm and Er3+/Yb3+: Li3Ba2La3(WO4)8 crystal with dimensions of 52 mm×24 mm×8 mm were obtained by the top-seeded solution growth (TSSG) method. Thermal expansion coefficients and thermal conductivity of both crystals were measured. The spectroscopic characterizations of both crystals were investigated. The spectroscopic analysis reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 52 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…Thus, numerous publications are devoted to triple molybdates and tungstates with the BaNd2(MoO4)4-type structure, which are represented by two families of compounds: LiMR2(MoO4)4 (M = K, Tl, Rb; R = Bi, Ln) and Li3Ba2Ln3(ХO4)8 (Х = Mo, W). The prospects for possible application of these compounds as photo-and IR-phosphors, materials for UV radiation dosimeters, laser materials are shown in [1][2][3][4][5][6][7][8][9][10]. The latter is also facilitated by the fact that the maximum anisotropy of thermal expansion in several representatives of this family is lower than that in other successfully used laser crystals [11].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, numerous publications are devoted to triple molybdates and tungstates with the BaNd2(MoO4)4-type structure, which are represented by two families of compounds: LiMR2(MoO4)4 (M = K, Tl, Rb; R = Bi, Ln) and Li3Ba2Ln3(ХO4)8 (Х = Mo, W). The prospects for possible application of these compounds as photo-and IR-phosphors, materials for UV radiation dosimeters, laser materials are shown in [1][2][3][4][5][6][7][8][9][10]. The latter is also facilitated by the fact that the maximum anisotropy of thermal expansion in several representatives of this family is lower than that in other successfully used laser crystals [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, compared with the large group of double tungstates (see, for example, Klevtsov & Klevtsova, 1977;Evdokimov et al, 1991), there exist only a few triple and more complex tungstates Li 3 Ba 2 R 3 (WO 4 ) 8 (R = La, Eu, Gd, Ho, Y) (Li et al, 2009(Li et al, , 2010(Li et al, , 2012Pan et al, 2012;Xiao et al, 2012b;Zeng et al, 2013;Hu et al, 2016;Guo et al, 2018) and Li 3 BaSrLa 3 (WO 4 ) 8 (Wei et al, 2015;Singh & Vaidyanathan, 2017), being filled derivatives of the BaNd 2 (MoO 4 ) 4 type (Kiseleva et al, 1979) and scheelite-like KBaLn(WO 4 ) 3 (Ln = Eu, Gd) (Xiao et al, 2012a;Wang et al, 2017), which are considered as promising laser hosts and phosphors for white LEDs. Recently we prepared a triple tungstate containing no trivalent metals, Cs 3 LiZn 2 (WO 4 ) 4 (Solodovnikov et al, 2017) which is a filled variant of the cation-deficient Cs 6 Zn 5 (MoO 4 ) 8 structure (Solodovnikov et al, 1987), and revealed a new group of silver-ion conducting triple tungstates Ag 1Àx Mg 1Àx R 1+x (WO 4 ) 3 (R = Sc, Al; 0-0.3 x 0.5) of the NASICON type (Kotova et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A biodegradable product shows ecological, scientific and economic importance [ 5 ]. Organic natural sorbents science as a branch of interdisciplinary field of physical chemistry has had explosive growth, on the theoretical and actual application of modern technologies [ 6 ]. Because of the background depletion of reserves on the planet, current research is aimed at using renewable raw materials and the production of biodegradable materials ( i.e.…”
Section: Introductionmentioning
confidence: 99%